Clinical Examination in Orthopedics - Iyer, K. Mohan. (Springer London : Imprint: Springer, 2012)
This book has been written step wise by enumerating various aspects of the importance of clinical examination derived by laying one’s hands on the affected part. By a thorough clinical examination, it can help an individual to arrive at a tentative differential diagnosis of the condition and hence help in investigating the same by numerous tests which are relevant to the given condition. The manner in which a given case is handled in this way is far more important than the diagnosis of the condition and this feature comes with practicing the same many times. It is a must for anyone embarking in life on Orthopedics as a career.